Microwave hyperthermia promotes caspase-3-dependent apoptosis and induces G(2)/M checkpoint arrest via the ATM pathway in non-small cell lung cancer cells - Zhao, Yan-Yan (Int J Oncol, 2018)
Post-operative microwave (MW) hyperthermia has been applied as an important adjuvant therapy to enhance the efficacy of traditional cancer treatment. A better understanding of the molecular mechanisms of MW hyperthermia may provide guided and further information on clinical hyperthermia treatment. In this study, we examined the effects of MW hyperthermia on non-small cell lung carcinoma (NSCLC) cells in vitro, as well as the underlying mechanisms. In order to mimic clinical treatment, we developed special MW heating equipment for this study. Various NSCLC cells (H460, PC-9 and H1975) were exposed to hyperthermia treatment using a water bath or MW heating system. The results revealed that MW hyperthermia significantly inhibited cell growth compared with the water bath heating system. Furthermore, MW hyperthermia increased the production of reactive oxygen species (ROS), decreased the levels of mitochondrial membrane potential (MMP) and induced caspase-3 dependent apoptosis. It also induced G(2)/M phase arrest through the upregulation of the expression of phosphorylated (p-) ataxia telangiectasia mutated (ATM), p-checkpoint kinase 2 (Chk2) and p21, and the downregulation of the expression of cdc25c, cyclin B1 and cdc2. On the whole, the findings of this study indicate that the exposure of NSCLC cells to MW hyper-thermia promotes caspase-3 dependent apoptosis and induces G(2)/M cell cycle arrest via the ATM pathway. This preclinical study may help to provide laboratory-based evidence for MW hyperthermia treatment in clinical practice.